Ease of market entry of Indian startups: formal and informal institutional influences - Scillitoe, Joanne L.; Birasnav, Muthuraj (South Asian Journal of Business Studies, 2021)
Purpose The purpose of this study offers a theoretical model, hypotheses and empirical analyses of how formal and informal institutions influence the ease of market entry of startups in the context of India. Design/methodology/approach A theoretical model based upon institutional and market entry theories is presented with hypotheses. Structural equation modeling is used to test the hypotheses. Findings Results of the study suggest that college preparations and a culture of creativity and innovation are positively related to ease of market entry by Indian startups. A culture of personal success is negatively related to ease of market entry. Government assistance related to ease of market entry is not significant. Originality/value This paper offers a new perspective, linking formal and informal institutional influences to startup ease of market entry. In addition, informal institutions are viewed from the cultures of personal success and creativity/innovation within the entrepreneurial domain, which is also new to the literature. This paper offers specific insights in the context of India startups and offers some interesting findings that can contribution to the literature, policy and practice.
Keywords: Culture; Entrepreneurship; India; Institutions; Market entry; Startup; dept.mgt; peer-reviewed

The relationship between quality management and innovativeness: an empirical study - Triana-Garcia, Randy; Muthuraj, Birasnav; Rincón-Guio, Cristian (6th South American Conference on Industrial Engineering and Operations Management, 2025)
This study aims to explore the relationship between four key elements of quality management: teamwork, feedback, motivational barriers, and need analysis, and their contribution to improve innovativeness in the Colombian educational context. Drawing on the concepts of control and learning in the quality management theory and using publicly available responses collected from the Colombian teachers who participated in the TALIS 2018 survey, this research study examines how teachers perceive these elements within their institutions and their potential impact on fostering innovativeness among teachers. The study adopts an empirical approach to analyze these relationships, employing a descriptive and inferential statistical framework to uncover patterns and correlations. By focusing on the school practices in Colombia, the research seeks to provide insights into how quality management practices can drive innovation in educational settings. Findings identify specific patterns in the implementation of these practices and their relationship with innovativeness among teachers, offering actionable recommendations for improving teaching strategies in education to improve quality. This study contributes to the broader understanding of management’s role in teaching and learning, offering valuable implications for policymakers and practitioners in developing countries. The novelty of this work lies in its analyses of TALIS data to assess quality management practices and their direct influence on fostering innovation.
Keywords: Business; Computer science; Empirical research; Knowledge management; Mathematics; Process management; Quality (philosophy); Statistics; dept.mgt